Grundtvig og Shakespeare - Bredsdorff, Morten (Grundtvig-studier, 1969)
Grundtvig and Shakespeare.By Morten Bredsdorff.Between 1829-31 Grundtvig made three journeys to England with the main purpose of studying the Anglo-Saxon manuscripts in London, Exeter, Oxford and Cambridge. The scientific results of these journeys, a better text of Beowulf and a challenge to British scholars to cultivate this field, are well known. The vivid impressions he received of a Liberal and industrialized England were, however, of far greater importance, as was his diligent reading of English literature from Chaucer to his own contemporaries Byron and Walter Scott. In his book Nordens Mythologi eller Sindbilled-Sprog (1832) Grundtvig recounts his impressions with great zest and humour. And here Shakespeare’s plays are of prime importance. Through Henrik Steffens Grundtvig had in his youth become familiar with the German romanticists’ boundless admiration for “ Shakespeare’s universal genius”. But his own knowledge of Shakespeare’s text was not very extensive as he did not have any command of English and had to be content with reading A. W. Schlegel’s German translation of the great Elizabethan.In England Grundtvig immersed himself with growing enthusiasm in Shakespeare’s plays in the poet’s own language. With delight he discovers that in his famous poem on the “ Sweet Swan of Avon” Ben Jonson has emphasized Shakespeare’s lack of erudition. Grundtvig here finds proof that as a son of the common people the poet has escaped the shackles of the despised Latin schooling and has given unbounded expression to the genuine spirit of the Anglo-Saxon people in his historical plays. Shakespeare now becomes an ally in the exposition of Grundtvig’s cultural policy and philosophy, according to which the peoples of northern Europe have been suppressed by classical humanism, and thus prevented from unfolding their original genius.According to Grundtvig, Shakespeare is an Anglo-Saxon genius, not in the German sense, but closely related to the Scandinavian spirit, and thus helps to illustrate the new popular cultural policy elaborated in this book.